How can we develop a model for the (re)design of more effective, valuable, and appealing educational systems? - Sprangers, Pieter Petrus Carolina (My University, 2022)
This thesis documents a research endeavor on the (re)design of educational systems. When learning is systemized, an educational system emerges. It is a complex system which according to stakeholders shows many deficiencies. The goal is to discover how to intervene systemically instead of solving isolated problems to generate better learning outcomes and a better learning experience. The fundamental literature review covers the specific character of scientific-educational design research as a new scientific discipline and how it can be applied to research educational systems. It further covers the construct of the learning experience. A model was developed for the (re)design of more effective, valuable, and appealing educational systems. The hypothesis is that the model can provide educational system designers with heuristics to (re)design educational systems to provide better learning outcomes and high-performing school systems. There will be a need for expert educational system designers to help schools to (re)design their educational system and make it more adaptive. A methodology of systemic design interventions embodied by a mix of experiments was used. The findings coming out of the experiments on nomadic learning, learning while moving, digital twin, and educational crafting revealed the positive impact of systemic interventions on the learning outcomes and learning experience and, are a partial foundation for the model. Further profound research is needed to reveal possible relations between elements of the model and deficiencies attributed to educational systems. To name some: what is the relation between the sedentary character of educational systems and bureaucracy? What is the relation between the pursuit of immortality and the fragility of the systems? What is the relation between the sedentary character of educational systems and the non-learning organization for staff members? What is the relation between closed educational systems and focus on generational learning? Our research showed that, when systemic interventions instead of problem-solving are realized via a well-thought-out system redesign, the learning capacity of the system, the learning experience, and learning outcomes of the agents improve. When the educational system is changed, the learning changes. Scientific educational design research proved to be an appropriate approach to investigate educational systems and what variables ‘educational system designers’ can take into account to (re)design educational systems.
Keywords: Educational systems; Organization of learning; Educational system-designer; Educational system-design model; Teaching; Learning